Analysis of habitat canopy cover for birds family bucerotidae with canopy capture in pocut meurah intan forest park, aceh besar. Issue 1 (1st December 2022) - Khairil,; Gagarin, Yuri; Abdullah,; Nurmaliah, Cut
Abstract: Pocut Meurah Intan Grand Forest Park (Tahura) is a form of nature conservation area which is overgrown by various types of plants that are widely used by bird species such as forage trees and nesting trees. Bird species from the Bucerotidae family are one of the fauna that take advantage of the presence of various types of plants in the area. When the existence of plants that function as feeding trees or nesting trees is threatened, the impact will be experienced by various bird species due to habitat changes such as a shortage of life-supporting plants. One of the factors that influence the use of trees in their habitat by birds is the density and canopy cover. The purpose of this study was to analyze the percentage of canopy cover for forage trees and bird nesting trees in the Bucerotidae family in Tahura Pocut Meurah Intan. Descriptive method is the method chosen in this study. The research location stations were determined using purposive sampling. To determine the canopy cover of forage trees and nesting trees, Canopycapture ver.1.0.2 software was used with the Hemispherical Photography method. Hemispherical Photography is a method by calculating the area of the canopy cover using a camera from under the tree canopy. This method produces more accurate data because the area captured by the camera is more specific so that it describes the actual tree canopy cover. Tree canopy cover data collection using Hemispherical Photography using the front camera of the XIAOMI Redmi Note 6 Pro mobile phone with a dual camera resolution of 20 and 2 megapixels with HD resolution (1, 280 x 720) at a point of taking photos. This technique is used in a 10 mx 10 m plot and analyzed using Microsoft office 2021 software. This research was conducted in January – February 2021 with a total of 2 stations. The results of this study found 14 species of forage trees and 13 species of nesting trees. The Moraceae family is more dominant in the use of birds from the Bucerotidae family as feed trees, while the Lauraceae family and also the Moraceae family are dominant as nesting trees. The value of tree canopy cover in Tahura Pocut Meurah Intan is 84.00% which belongs to the solid category.